Prognostic and Immunological Role of FUN14 Domain Containing 1 in Pan-Cancer: Friend or Foe? - Yuan, Qingchen; Sun, Na; Zheng, Jiayu; Wang, Yingxuan; Yan, Xiaole; Mai, Wuqian; Liao, Yuhua; Chen, Xiao (Frontiers in Oncology, 2020)
Background: FUN14 domain containing 1 (FUNDC1) plays a pivotal role in mitochondrial autophagy (mitophagy), which is closely associated with human immunity. However, the role of FUNDC1 in cancers remains unclear. This study aimed to visualize the prognostic landscape of FUNDC1 in pan-cancer and investigate the relationship between FUNDC1 expression and immune infiltration. Methods: In this study, we explored the expression pattern and prognostic value of FUNDC1 in pan-cancer across multiple databases, including ONCOMINE, PrognoScan, GEPIA, and Kaplan-Meier Plotter. Then, using the GEPIA and TIMER databases, we investigated the correlations between FUNDC1 expression and immune infiltration in cancers, especially liver hepatocellular carcinoma (LIHC), and lung squamous cell carcinoma (LUSC). Results: In general, compared with that in normal tissue, tumor tissue had a higher expression level of FUNDC1. Although FUNDC1 showed a protective effect on pan-cancer, a high expression level of FUNDC1 was detrimental to the survival of LIHC patients. Although different from what was found for LUSC, for LIHC, there were significant positive correlations between FUNDC1 expression and immune infiltrates, including B cells, CD8+ T cells, CD4+ T cells, neutrophils, macrophages, and dendritic cells. Furthermore, markers of infiltrating immune cells, such as tumor-associated-macrophages (TAMs), exhibited different FUNDC1-related immune infiltration patterns. Conclusion: The mitophagy regulator FUNDC1 can serve as a prognostic biomarker in pan-cancer and is correlated with immune infiltrates.